The Invisible Threat of Non-steroidal Anti-inflammatory Drugs for Kidneys - Clavé, Stéphanie; Rousset-Rouvière, Caroline; Daniel, Laurent; Tsimaratos, Michel (Frontiers in Pediatrics, 2019)
Background. Non-steroidal anti-inflammatory drugs (NSAIDs) are often used as analgesic and antipyretic drugs. Nephrotoxicity is a common side effect and leads in 1–5% of pediatric cases to acute kidney injury (AKI). The nephrotoxic effects of NSAIDs arise mainly from two pathological mechanisms: 1) acute tubulo-interstitial nephritis (ATIN) following immune reaction and 2) prerenal failure because of reduced renal plasma flow. Histological examinations are required to confirm the pathomechanism of AKI after NSAID exposure. The aim of this study was to illustrate the risk of ATIN in children with AKI after NSAID exposure. Results. The medical records of all 100 pediatric patients with biopsy-proven AKI treated between January 2006 and 2016 at La Timone Hospital, Marseille, France, were analyzed retrospectively. Twenty-five of these patients had ATIN, four of which were healthy children who had been treated with NSAIDs. In other words, NSAID side effects accounted for 4% of all cases of biopsy-proven AKI and 16% of all cases of ATIN. “None of the patients had hypovolemia when they received NSAIDs”. Clinical symptoms were non-specific. All patients had abdominal pain and vomiting but normal urine volume output. Maximum serum creatinine levels ranged from 300 to 512 μmol/l, with estimated minimum creatinine clearances of 12 to 26 ml/min/1.73m2. None of the patients had significant proteinuria. One child had hyperechogenic enlarged kidneys. Three patients were treated with steroids, one of whom also received intravenous methylprednisolone. Renal function improved gradually in all patients, but the patient who received methylprednisolone developed moderate chronic kidney disease. Conclusions. Biopsy proven-AKI secondary to NSAID use can be severe and be associated with ATIN. Since NSAID-induced ATIN can lead to chronic kidney disease, clinicians using NSAIDs should focus on preventing AKI.